Higher nicotine dependence and greater smoking abstinence in parental than non-parental smokers: a secondary analysis of smoking cessation trials - Ge, Yiran; Li, Mengyao; Luk, Tzu Tsun; Cheung, Derek Yee Tak; Guo, Ningyuan; Tong, Henry Sau Chai; Lai, Vienna Wan Yin; Chan, Sophia Siu Chee; Wang, Man Ping; Zhao, Shengzhi (Frontiers in Public Health, 2025)
ObjectiveParental smokers account for approximately one-third of smokers worldwide and often exhibit distinct smoking and quitting behaviors compared to non-parental smokers. Understanding these differences is crucial for developing targeted cessation interventions; however, current evidence remains limited.MethodsThis secondary analysis pooled individual participant data from 10 community-based smoking cessation trials conducted in Hong Kong between 2010 and 2020 (N = 10,871 adult daily smokers). We compared parental smokers (those with at least one child) and non-parental smokers in terms of sociodemographic characteristics, smoking behaviors, nicotine dependence (Heaviness of Smoking Index), quitting motivation, and cessation outcomes at 6 months post-intervention. Outcomes included biochemically validated abstinence (exhaled carbon monoxide <4 ppm and salivary cotinine <10 ng/mL) and self-reported 7-day point-prevalence abstinence (PPA). Multivariable regression models were adjusted for age, sex, education, income, and trial year.ResultsOf the participants, 42.2% were parental smokers, who were older and had lower education and income (all p < 0.001). They had higher daily cigarette consumption (mean: 14.8 vs. 12.9, adjusted β = 1.59, p = 0.004) and higher nicotine dependence (9.2% vs. 5.9%, AOR = 1.36, p < 0.001). A large number of parental smokers had past quit attempts (61.8% vs. 54.0%, AOR = 1.25, p < 0.001) and intentions to quit within 30 days (61.2% vs. 46.4%, AOR = 1.31, p < 0.001). At 6 months, parental smokers showed higher validated abstinence (7.7% vs. 5.9%, AOR = 1.37, p < 0.001) and self-reported 7-day PPA (15.6% vs. 13.9%, AOR = 1.21, p = 0.002). Among parental smokers, those co-living with children had greater abstinence than those not necessarily co-living, for both self-reported 7-day PPA (AOR = 1.43, 95% CI 1.03–1.98, p = 0.032) and validated abstinence (AOR = 1.62, 95% CI 1.04–2.52, p = 0.032).ConclusionParental smokers showed higher nicotine dependence but greater motivation and higher abstinence rates following brief community-based interventions. Tailored programs should address their elevated addiction while leveraging their motivation to enhance cessation success.